Phosphorus limitation heightens vulnerability of Crocosphaera watsonii to ocean warming compared with iron limitation - Mansour, Amjad A.; Gholmieh, Laura M.; Gholmieh, Ellya C.; Duan, Ran; Bian, Xiaopeng; Chen, Yutong; John, Seth G.; Hutchins, David A.; Fu, Fei-Xue (Frontiers in Microbiology, 2026)
IntroductionPhytoplankton rely on diazotrophs like the globally important Crocosphaera watsonii to provide bioavailable nitrogen through nitrogen fixation. Given predicted global warming and oligotrophic scenarios, we investigated how nutrient limitation modulates C. watsonii’s response to ocean warming, to better understand future marine ecosystem health.MethodsWe performed complete temperature curves (20–34 °C) under three nutrient conditions [iron (Fe)-limited, phosphorus (P)-limited, and Fe/P-replete] to compare physiological responses and test previously hypothesized temperature-nutrient interactions.ResultsAcross the viable temperature range, replete culture growth and fixation rates showed narrower, unimodal-like curves, contrasting the greater plateauing witnessed in nutrient-limited thermal curves. Under both limitations, nitrogen fixation was more impacted than carbon fixation. Fe-limited cultures performed better at higher temperatures (survival range: 22–34 °C) and shared thermal optima with replete cultures for growth rates (28–32 °C), while P-limited cultures performed better at lower temperatures (survival range: 20–32 °C) with a narrower optimum range (28–30 °C). Furthermore, extreme temperatures appear to outweigh and override nutrient limitation effects at the warmer end for Fe-limited cultures (34 °C) and the cooler end for P-limited cultures (20 °C), as no significant differences were observed between limited and replete cultures for both growth and fixation rates at these temperatures.DiscussionGiven predicted sea temperature increases and the rising frequency and intensity of oceanic heat waves, our results suggest that C. watsonii in P-limited regimes like the North Atlantic may be more vulnerable to warming than in Fe-limited regimes like the North Pacific. P-limitation may force C. watsonii to migrate to higher, cooler latitudes for survival, possibly leaving lower-latitude phytoplankton and ecosystems more vulnerable to nitrogen limitation.